Systemic Usury and the European Consumer Credit Directive - Doris Neuberger; Udo Reifner (Vierteljahrshefte zur Wirtschaftsforschung, 2020)
Usury is a frequent occurrence in consumer credit markets and particularly affects low-income households. Although the term usury conjures images of a greedy individual consciously acting to exploit the weak bargaining position of another by deceitful and even fraudulent means, we consider it as a systemic issue: as a problem of social discrimination, where belonging to a group which is statistically discriminated against leads to entrapment in a chain of usurious credit and financial contracts. This paper reviews the economic rationale for usury legislation and evaluates the European Consumer Credit Directive 2008/48/EC in this context. It identifies systemic usury as the product of market failure: the most powerful explanations for which are monopoly power, where the consumer is locked in a bilateral credit relationship; discrimination through risk-based pricing, and negative externalities. Contrary to the main focus of the European Consumer Credit Directive, improved disclosure of contract terms and other relevant information to consumers at the point of contracting cannot address systemic usury in credit markets. Even fully informed consumers can be discriminated against and become trapped in a situation of bilateral monopoly. As a consequence, the Directive is found to be ineffective: it implicitly acknowledges usurious practices and products as legal and undermines the national fight against usury. The Directive must be reformed. – – Wucher ist ein häufiges Phänomen auf den Verbraucherkreditmärkten und betrifft insbesondere Haushalte mit niedrigem Einkommen. Obwohl der Begriff Wucher Bilder eines gierigen Individuums beschwört, das bewusst handelt, um die schwache Verhandlungsposition eines anderen mit irreführenden und sogar betrügerischen Mitteln auszunutzen, betrachten wir ihn als systemisches Problem: als ein Problem der sozialen Diskriminierung, bei dem die Zugehörigkeit zu einer statistisch diskriminierten Gruppe zu einer Einklemmung in eine Kette von wucherischen Kredit- und Finanzverträgen führt. Dieses Papier untersucht die ökonomischen Argumente für die Wuchergesetzgebung und bewertet in diesem Zusammenhang die Europäische Verbraucherkreditrichtlinie 2008/48/EG. Es identifiziert systemischen Wucher als das Ergebnis von Marktversagen: Die überzeugendsten Erklärungen dafür sind Monopolmacht, bei der der Verbraucher in einer bilateralen Kreditbeziehung gefangen ist, Diskriminierung durch risikoorientierte Preisgestaltung und negative Externalitäten. Im Gegensatz zum Hauptaugenmerk der Europäischen Verbraucherkreditrichtlinie kann eine verbesserte Offenlegung von Vertragsbedingungen und anderen relevanten Informationen für die Verbraucher zum Zeitpunkt der Vertragsunterzeichnung nicht auf systemischen Wucher auf den Kreditmärkten abzielen. Selbst voll informierte Verbraucher können diskriminiert werden und in einer Situation des bilateralen Monopols gefangen sein. Infolgedessen erweist sich die Richtlinie als unwirksam: Sie erkennt implizit wucherische Praktiken und Produkte als legal an und untergräbt die nationale Bekämpfung von Wucher. Die Richtlinie muss reformiert werden.
Keywords: D14; D18; D42; D62; D63; G21; G28; G51; K15; K22; K33; L12; L14; 330; Discrimination; Consumer Credit Directive; incomplete information; payment protection insurance; overindebtedness; monopoly power; responsible lending; risk-based pricing; usury